2021
DOI: 10.1007/s00784-021-04007-2
|View full text |Cite
|
Sign up to set email alerts
|

Partial pulpotomy without age restriction: a retrospective assessment of permanent teeth with carious pulp exposure

Abstract: Objectives This study aimed to retrospectively evaluate clinical and radiographic outcomes of partial pulpotomy performed in permanent teeth with carious pulp exposure. Materials and methods Records of patients undergoing treatment at an undergraduate dental clinic between 2010 and 2019 were screened for partial pulpotomies in teeth with a presumptive diagnosis of normal pulp or reversible pulpitis. The follow-up had to be ≥ 1 year. Patient data were retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Another long-term study showed that at the end of the follow-up period (12 months), the success of complete pulpotomy in the occlusal and proximal caries group was 95% and 92.5%, respectively (p = 0.644) [31] . Finally, the overall success rate in maintaining pulp vitality in this study was 89.1%, with a tooth survival of 98.4% [32] .…”
Section: Mature Teethmentioning
confidence: 52%
“…Another long-term study showed that at the end of the follow-up period (12 months), the success of complete pulpotomy in the occlusal and proximal caries group was 95% and 92.5%, respectively (p = 0.644) [31] . Finally, the overall success rate in maintaining pulp vitality in this study was 89.1%, with a tooth survival of 98.4% [32] .…”
Section: Mature Teethmentioning
confidence: 52%
“…Pulpotomy has traditionally not been part of the treatment considerations for mature permanent teeth diagnosed with irreversible pulpitis. However, there is now increasing evidence from retrospective studies, 54,55,56 prospective cohort studies 40,41,47,57,58,59,60 and randomised controlled trials, 39,42,43,44,45,46,61,62,63,64,65,66,67,68,69,70 showing high success rates for pulpotomy in treating mature permanent teeth with irreversible pulpitis or carious pulp exposures (online Supplementary Table 1). Systematic reviews, meta-analyses and recent umbrella reviews (Table 2) have also concluded that pulpotomy could be a prospective substitute to conventional RCTx in managing vital mature permanent teeth diagnosed with irreversible pulpitis or carious pulp exposure.…”
Section: State Of Evidencementioning
confidence: 99%
“…Früher wurde angenommen, dass vitalerhaltende Maßnahmen bei älteren Patienten, deren Pulpagewebe verglichen mit jenem von jüngeren Patienten weniger zellreich ist, ungünstigere Erfolgsaussichten hätten. Wenngleich das Pulpagewebe im jungen Alter tatsächlich ein höheres Regenerationspotenzial besitzt, weisen Studien darauf hin, dass das Patientenalter keinen signifikanten Einfluss auf die Erfolgswahrscheinlichkeit einer partiellen Pulpotomie hat 15 , 16 . Auch das Stadium des Wurzelwachstums beeinflusst die Prognose nicht wesentlich 15 .…”
Section: Erfolgsaussichten Vitalerhaltender Maßnahmen Und Mögliche Ei...unclassified